FAKTOR-FAKTOR KESEHATAN KERJA TERHADAP PENINGKATAN PERSONAL HYGIENE PADA PETUGAS PENGANGKUT SAMPAH DI KOTA GORONTALO - Hartati Inaku; Moh Malik A Hanafi (Akademika, 2019)
The purpose of this study was to determine the Factors Affecting Occupational Health in Improving Personal Hygiene in Garbage Transport Officers in the City of Gorontalo. The research design uses Analytic Survey with Cross Sectional approach. Sampling using Accidental Sampling technique with a sample of 50 respondents. Analysis of the study used a chi square test with a significant α = 0.05, the results obtained p value = 0.001 (<0.05) which means there is an influence of knowledge with occupational health in improving personal hygiene, then the value of p value = 0.416 (<0, 05) which means there is no influence of work period with occupational health in improving personal hygiene and the value of p value = 0,000 (<0.05) which means there is an influence of the use of personal protective equipment (PPE) with occupational health in improving personal hygiene in the garbage transport officer in Gorontalo City.Tujuan penelitian ini adalah untuk mengetahui Faktor-faktor yang Mempengaruhi Kesehatan Kerja Dalam Peningkatan Personal Hygiene Pada Petugas Pengangkut Sampah di Wilayah Kota Gorontalo. Desain penelitian menggunakan Survey Analitik dengan pendekatan Cross Sectional. Pengambilan sampel menggunakan tekhnik Accidental Sampling dengan sampel 50 responden. Analisis penelitian menggunakan uji chi square dengan signifikan α = 0,05, hasil didapatkan p value = 0,001 (<0,05) yang berarti terdapat pengaruh pengetahuan dengan kesehatan kerja dalam peningkatan personal hygiene, kemudian didapatkan nilai p value = 0,416 (<0,05) yang berarti tidak terdapat pengaruh masa kerja dengan kesehatan kerja dalam peningkatan personal hygiene dan nilai p value = 0,000 (<0,05) yang berarti terdapat pengaruh pemakaian alat pelindung diri (APD) dengan kesehatan kerja dalam peningkatan personal hygiene pada petugas pengangkut sampah di Kota Gorontalo